Analysis of Binary Aluminium-Magnesium products with varying composition and optimum flowability, tensile strength and hardness - Surianis, Mat Salleh (Universiti Malaysia Perlis, 2009)
Casting is a process that can produce a complex and complicated component. This final year project is to investigate how far the influence on mechanical properties and microstructure of varying aluminium-magnesium alloy using CO2 molding process. In this research, three samples with different composition were prepared into casting method and determine its properties. Main parameter used in this process is varying composition between aluminium and magnesium. Purpose of this research is to see the changes of the mechanical characteristic and microstructure base on different composition according to Aluminium alloys. This present investigation deals with preparing aluminium alloy from a mixture of aluminium and magnesium in three different composition which are Al91wt%Mg9wt%, Al80wt%Mg20wt% and Al72wt%Mg28wt%. This investigation was two pronged. In the first stage, the aluminium alloy was melt in electric furnace. The melting was done at 750 °C as it was to make sure that resulted in better wet ability of aluminium alloy particles and reduced entrapment of gases in the cast. The second part of this investigation involved evaluation of microstructure and properties of this alloy in as cast and heat-treated conditions. Mechanical characteristic quality that will be consider, which are of major concern, included tensile strength, hardness and flow ability, while microstructure analysis is to see the microstructure changes. Tensile and hardness test will help to obtain grain sizes of Al-Mg alloys. The flowability at each given composition level will be determinate to be used in various production criteria.